2018
DOI: 10.1002/hep.29639
|View full text |Cite
|
Sign up to set email alerts
|

Optimal threshold of controlled attenuation parameter with MRI‐PDFF as the gold standard for the detection of hepatic steatosis

Abstract: The cut-point of CAP for presence of hepatic steatosis (MRI-PDFF ≥ 5%) was 288 dB/m. The diagnostic accuracy of CAP for the detection of hepatic steatosis is more reliable when the IQR of CAP is <30 dB/m. These data have implications for the clinical use of CAP in the assessment of NAFLD. (Hepatology 2018;67:1348-1359).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
272
2
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 289 publications
(285 citation statements)
references
References 57 publications
9
272
2
2
Order By: Relevance
“…In a sensitivity analysis, considering the value of 288 dB/m as recently proposed for the diagnosis of NAFLD, the prevalence of fatty liver was lower, ie, 27.2%. On multivariate analyses we confirmed age ≥50 years (OR: 1.73, C.I.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In a sensitivity analysis, considering the value of 288 dB/m as recently proposed for the diagnosis of NAFLD, the prevalence of fatty liver was lower, ie, 27.2%. On multivariate analyses we confirmed age ≥50 years (OR: 1.73, C.I.…”
Section: Resultsmentioning
confidence: 96%
“…Caussy et al recently found that CAP can lead to a significant rate of misclassification for fatty liver. They also proposed a threshold of 288 dB/m for the diagnosis of steatosis by using as reference method magnetic resonance imaging and not the histology from biopsy specimens . Using the Caussy reference value for CAP, the prevalence of fatty liver in our population was about 27%.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Overall literature suggests that CAP measurement correlates with the histological severity of hepatic steatosis . Furthermore, in patients at risk, CAP measurement, when technically reproducible, has a good diagnostic accuracy to diagnose NAFLD, when MRI‐PDFF is used as the reference . Given the wide availability and the low costs, future studies are warranted to examine the utility of hepatic fat content monitoring by CAP measurement in clinical practice.…”
Section: Imaging Studiesmentioning
confidence: 99%